Draft Genome Sequence Data of Streptomyces anulatus, Strain K-31 - Andrey P. Bogoyavlenskiy; Madina S. Alexyuk; Amankeldi K. Sadanov; Vladimir E. Berezin; Lyudmila P. Trenozhnikova; Gul B. Baymakhanova (Data, 2023)
Streptomyces anulatus is a typical representative of the Streptomyces genus synthesizing a large number of biologically active compounds. In this study, the draft genome of Streptomyces anulatus, strain K-31 is presented, generated from Illumina reads by SPAdes software. The size of the assembled genome was 8.548838 Mb. Annotation of the S. anulatus genome assembly identified C. hemipterus genome 7749 genes, including 7149 protein-coding genes and 92 RNA genes. This genome will be helpful to further understand Streptomyces genetics and evolution and can be useful for obtained biological active compounds.